Civil Society and Human Right Protection in Africa: A Comparative Study of South Africa and Nigeria - ANYALEBECHI, Shammah Mahakwe, PhD; Amabibi, Ferdinand, PhD; Hart, Akie Opuene, PhD; Eyina, Nkatomba, PhD (Zien Journals, 2023)
Civil Society Organizations (CSOs) play a crucial role in advocating for and protecting human rights across Africa. However, they face numerous challenges that hinder their effectiveness and the overall human rights situation across the continent. Therefore, the paper focused on the roles of Civil Society and Human Right Protection in Africa: A Comparative Study of South Africa and Nigeria. The paper was anchored on the civil society theory; and a qualitative research design was adopted for the study. Data were gathered through secondary sources which were subjected to content analysis. The paper highlighted the significant role that CSOs in South Africa and Nigeria have played in advocating for human rights and socio-political changes. However, CSOs in South Africa and Nigeria face a wide range of complex challenges in their efforts to promote and protect human rights, including political interference, restrictive legislation, lack of funding, capacity constraints, and public mistrust. Despite these challenges CSOs have shown resilience, emphasizing their central role in advancing social justice and democratic governance. Overcoming these hurdles, the paper recommended that there is need to improve the capacity and effectiveness of CSOs in South Africa and Nigeria through capacity building, funding and resource diversification, fostering an enabling legal environment, strategic collaboration, promoting transparency and accountability, and protecting civil society space. These initiatives will bolster the ability of CSOs to effectively advocate for and protect human rights
Keywords: Civil Society; Democracy; Human Rights